The Palgrave Handbook of Positive Education - Kern, Margaret L.; Wehmeyer, Michael L. (Springer Nature, 2021)
This open access handbook provides a comprehensive overview of the growing field of positive education, featuring a broad range of theoretical, applied, and practice-focused chapters from leading international experts. It demonstrates how positive education offers an approach to understanding learning that blends academic study with life skills such as self-awareness, emotion regulation, healthy mindsets, mindfulness, and positive habits, grounded in the science of wellbeing, to promote character development, optimal functioning, engagement in learning, and resilience. The handbook offers an in-depth understanding and critical consideration of the relevance of positive psychology to education, which encompasses its theoretical foundations, the empirical findings, and the existing educational applications and interventions. The contributors situate wellbeing science within the broader framework of education, considering its implications for teacher training, education and developmental psychology, school administration, policy making, pedagogy and curriculum studies. This landmark collection will appeal to researchers and practitioners working in positive psychology, educational and school psychology, developmental psychology, education, counselling, social work and public policy.